Kritische Lektionen - Burkhardt, Laura; Hierdeis, Helmwart; Hug, Theo (innsbruck university press, 2017)
"Critical Lessons" is overriding the contributions here, which deal with the discriminating, enlightening, resistant, and innovative functions of critique, in relation to a wide range of social science topics. On the occasion of his departure from the University of Innsbruck, the authors want to express their thanks, appreciation and respect for his scientific and academic achievements in life - also for having opened his eyes to them and many others for some, even uncomfortable truths.